Assessing the functionality of an emergency obstetric referral system and continuum of care among public healthcare facilities in a low resource setting: an application of process mapping approach - Bernice Ofosu; Dan Ofori; Michael Ntumy; Kwaku Asah-Opoku; Theodore Boafor (BMC, 2021)
Abstract Background Weak referral systems remain a major concern influencing timely access to the appropriate level of care during obstetric emergencies, particularly for Low-and Middle-Income Countries, including Ghana. It is a serious factor threatening the achievement of the maternal health Sustainable Development Goal. The objective of this study is to establish process details of emergency obstetric referral systems across different levels of public healthcare facilities to deepen understanding of systemic barriers and preliminary solutions in an urban district, using Ablekuma in Accra, Ghana as a case study. Methods The study is an analytical cross-sectional study. Nine [1] targeted interviews were carried out for a three-week period in June and July 2019 after informed written consent with two [2] Obstetrics & Gynaecology consultants, two [2] Residents, one family physician, and four [3] Midwives managing emergency obstetric referral across different levels of facilities. Purposeful sampling technique was used to collect data that included a narration of the referral process, and challenges experienced with each step. Qualitative data was transcribed, coded by topics and thematically analysed. Transcribed narratives were used to draft a process map and analyze the defects within the emergency obstetric referral system. Results Out of the 34 main activities in the referral process within the facilities, the study identified that 24 (70%) had a range of barriers in relation to communication, transport system, resources (space, equipment and physical structures), staffing (numbers and attitude), Healthcare providers (HCP) knowledge and compliance to referral policy and guideline, and financing for referral. These findings have implication on delay in accessing care. HCP suggested that strengthening communication and coordination, reviewing referral policy, training of all stakeholders and provision of essential resources would be beneficial. Conclusion Our findings clearly establish that the emergency obstetric referral system between a typical teaching hospital in an urban district of Accra-Ghana and peripheral referral facilities, is functioning far below optimum levels. This suggests that the formulation and implementation of policies should be focused around structural and process improvement interventions, strengthening collaborations, communication and transport along the referral pathway. These suggestions are likely to ensure that women receive timely and quality care.